2014
DOI: 10.1002/ddr.21232
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Diacerhein and Antiepileptic Drugs After Local Peripheral, and Oral Administration in the Rat Formalin Test

Abstract: Preclinical Research The present study was designed to evaluate the possible antinociceptive interaction between diacerhein and some antiepileptic drugs (carbamazepine, topiramate and gabapentin) on formalin-induced nociception. Diacerhein, each of the antiepileptics or a fixed dose-ratio combination of these drugs was assessed after local peripheral and oral administration in rats. lsobolographic analyses were used to define the interaction between drugs. Diacerhein, antiepileptic drugs (carbamazepine, topira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…Commonly reported adverse effects of topiramate are dizziness, ataxia, and disorientation 36 . However, previous data of our group indicates that topiramate did not alter rota-rod performance at doses employed here 9 . In fact, Shank et al 37 reported the same effect of this drug even in doses higher than 2000 mg/kg.…”
Section: Antinociceptive Effect Of Topiramate and Ketorolac Combinationcontrasting
confidence: 67%
“…Commonly reported adverse effects of topiramate are dizziness, ataxia, and disorientation 36 . However, previous data of our group indicates that topiramate did not alter rota-rod performance at doses employed here 9 . In fact, Shank et al 37 reported the same effect of this drug even in doses higher than 2000 mg/kg.…”
Section: Antinociceptive Effect Of Topiramate and Ketorolac Combinationcontrasting
confidence: 67%
“…In addition to the release of various inflammatory mediators, formalin can also activate TRPA1 directly to elicit pain and inflammation . This test has been successfully used to assess the efficacy of a variety of compounds like morphine, oxyphenylbutazone, acetylsalicylic acid, corticosteroids , diflunisal , diacerhein, carbamazepine, topiramate, and gabapentin . Antagonists targeting TRPA1 ion channels , NMDA receptors , and neurokinin‐1 receptors have also been examined.…”
Section: Models Of Cutaneous Painmentioning
confidence: 99%
“…The doses of GBP used in our study (4.6–16.8 μg/kg) are significantly less than the oral dosages (ca. 25 mg/kg) commonly used in animal models of pain . Even at such a low dose, however, GBP could produce antimetastatic effects.…”
Section: Discussionmentioning
confidence: 99%